ExoMol molecular line lists XXX: a complete high-accuracy line list for water. Issue 2 (14th August 2018) - Polyansky, Oleg L; Kyuberis, Aleksandra A; Zobov, Nikolai F; Tennyson, Jonathan; Yurchenko, Sergei N; Lodi, Lorenzo
ABSTRACT: A new line list for H$_2^{\, 16}$ O is presented. This line list, which is called POKAZATEL, includes transitions between rotational–vibrational energy levels up to 41 000 cm −1 and is the most complete to date. The potential energy surface (PES) used for producing the line list was obtained by fitting a high-quality ab initio PES to experimental energy levels with energies of 41 000 cm −1 and for rotational excitations up to J = 5. The final line list comprises all energy levels up to 41 000 cm −1 and rotational angular momentum J up to 72. An accurate ab initio dipole moment surface was used for the calculation of line intensities and reproduces high-precision experimental intensity data with an accuracy close to 1 per cent. The final line list uses empirical energy levels, whenever they are available, to ensure that line positions are reproduced as accurately as possible. The POKAZATEL line list contains over 5 billion transitions and is available from the ExoMol website (www.exomol.com ) and the CDS data base.